Pengambilan Keputusan Dengan Pendekatan Analytical Hierarchy Process (AHP) Studi Kasus pada Pengembangan Kawasan Situ Pulo, Bekasi - Pitri Yandri (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
In the era of autonomy, swamp (situ) is the one of property that could be managed by the local government in order to raise their revenues (PAD). However, in order to maximize its PAD, the decisions made by local governments usually faced with a complex situation. The research objective is to assess the perceptions and preferences of stakeholders that include the public, private sector and government towards the development of swamp. One of the eighteen swamps in Bekasi is